Investigating the attitude of psychiatrists towards the presence of stigma about COVID-19 - Moradi-Gorabpasi, Farhoud; Khademi, Mojgan; Taghva, Arsia; Shakeri, Shirin; Panaghi, Leili (Frontiers in Psychiatry, 2025)
IntroductionThe COVID-19 pandemic has led to significant global disruption, resulting in increased stigma and discrimination towards certain communities and populations affected by the virus. Given that psychiatrists play a crucial role in both preventing and treating the complications associated with disease-related stigma, this study aims to examine their attitude towards the stigma associated with COVID-19.MethodsThis research utilized a cross-sectional survey design to evaluate psychiatrists' attitudes towards COVID-19 stigma. We used a 15-item researcher-made questionnaire with scores ranging from 15 to 75. The questionnaire was distributed to 131 psychiatrists in Tehran (capital city of Iran) from April 9, 2023 to May 26, 2023, with responses collected voluntarily. Data were analyzed with descriptive statistics, independent t-tests, and one-way ANOVA to evaluate stigma attitudes across demographic variables using SPSS software (version 25).ResultsThe Cronbach's alpha for the COVID-19 Stigma Attitude Scale for Psychiatrists (CSASP) was determined to be 0.861, indicating strong reliability. Moreover, all questions achieved acceptable corrected item-total correlation values above 0.2. It was revealed that the highest and lowest recorded scores were 68 and 25, respectively (average 51.16 ± 8.83). Also 19 individuals (14.5%) exhibited a weak attitude, 41 individuals (31.3%) displayed a rather weak attitude, 54 individuals (41.2%) showed a rather strong attitude, and 17 individuals (13%) demonstrated a strong attitude toward the presence of COVID-19 stigma. Furthermore, 96 individuals (73.3%) recognized stigma surrounding COVID-19 at the onset of the pandemic; of these, 11 (11.5%) disagreed with the idea of current stigma, while 18 (18.7%) had no opinion. Thus, 67 participants (69.8%) still believe such a stigma exists. Finally, 83 respondents (63.3%) acknowledged stigma related to AIDS and leprosy, with 53 (63.8%) of them also believing in the stigma surrounding COVID-19.ConclusionThe findings highlighted various attitudes towards the ongoing stigma associated with COVID-19, with most psychiatrists recognizing its persistence throughout the pandemic. The research also points to the interconnectedness of stigma across different diseases, emphasizing common societal factors like fear, misinformation, and cultural biases. This underscores the crucial role psychiatrists play in addressing stigma and its effects on society.